Penerapan Pertanian Organik di Lembang Buntu La’bo’ Kecamatan Sanggalangi’ Kabupaten Toraja Utara - Desi Ruru; Anes Monika; Mesylin Linggi; Lisa K. Wibisono (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The application of organic farming has potential in the agricultural sector. There is a lot of empty land, adequate water sources, good soil conditions. However, it can be seen from the results of the survey we conducted that there is a lack of concern for the surrounding community and inadequate support by good management with human resources even though there is great potential in the area. So we, PKM, act as a driving force, providing understanding to the community regarding the potential that exists in the area.